Dinamika Cinta pada Pasangan Lesbian - Aisyatin Kamila; Casmini Casmini (Universitas Muhammadiyah Jember, 2020)
This study aimed to describe the dynamics of lesbian love using descriptive qualitative method. The participants consisted of two obtained by purposive sampling and are willing to be. The criteria of the participants are characteristics according to the lesbi individual which leads to lesbi behavior and has an impact on the dynamics of love experienced by lesbi. Techniques of data retrieval is done using in-depth interviews, observation, and study the documents. Results of the study are presented in two major themes, the first of which the past leads to lesbian behavior, then the second is to bring together the admiration of love, romance until the conflict experienced by lesbian couples.